Islamic Perspectives on Cybersecurity and Data Privacy: Legal and Ethical Implications - Koko Komaruddin; Andrew Shandy Utama; Eko Sudarmanto; Sugiono Sugiono (Westscience Press, 2023)
In the rapidly evolving landscape of cybersecurity and data privacy, the interface between culture, ethics, and law plays a pivotal role. This study delves into